ANALISIS INSTAGRAM MARKETING DAN KUALITAS PRODUK TERHADAP CITRA MERK PADA RUMAH MAKAN PADANG PAYAKUMBUAH - Muhamad Ramadhan (2023)
Technological developments that have occurred have made changes in terms of carrying out a business, one of the technological developments that can affect is the emergence of social media. Now the use of social media is widely used in marketing, one of which is used to influence brand image. A positive brand image is an added value for a company, because by having a positive brand image, consumers will make the brand their choice. Building a positive brand image cannot only be done through social media, but also by making the products produced have good quality. This study aims to determine the effect of Instagram marketing and product quality on brand image at Padang Payakumbuah Restaurant. The analytical method used in this study is Partial Least Square (PLS). The results of the analysis that has been done can be concluded that Instagram marketing does not have a significant effect on brand image. The results of the analysis that has been done can be concluded that product quality has a significant influence on brand image.